Variabilidad, tendencia y eventos extremos en los rendimientos agrícolas a nivel de partidos en la Provincia de Buenos Aires - Cabrini, Silvina María (2022)
Climate variability is the main determinant of fluctuations in the productive and economic results of agriculture. Due to Climate Change, extreme events are expected to occur with greater frequency and intensity in the coming years. Given this scenario, studies related to the effects of climate variability on agricultural production are of special interest. This study analyzes the time series of yields at the party level of the main crops in the province of Buenos Aires, in the period 2000/01-2020/21. The trend and occurrence of extreme values ​​in wheat, corn and soybean yields are identified. The frequencies of extreme values ​​are related to the phases of the ENSO phenomenon (El Niño-Southern Oscillation) observed for each campaign. The economic values ​​of the losses/gains in the production of the three crops are estimated with respect to the expected values ​​for each campaign. Yields show significant positive trends in 78%, 46%, and 30% of the matches for wheat, corn, and soybeans, respectively. There is a significant relationship between the frequencies of extreme yield values ​​and the ENSO phases, this relationship being more important in summer crops. In particular, a relative frequency of 38 and 41% stands out for extremely low or very low yields, in campaigns classified as the second consecutive La Niña, for corn and soybean, respectively. While the frequencies of extremely low or very low yields in campaigns classified as a neutral year or El Niño are between 0% - 3%. Regarding the economic value of the harvests of the three crops, the differences between the values ​​obtained vs. accumulated in the period, are positive values ​​of +3,285 and +872 million USD in “El Niño” years for the northern and southern regions, respectively, and negative values ​​of -3,387 and -388 million USD, in “La Niña” years for both areas respectively. The results provide evidence on the potential value of ENSO-based seasonal forecasts for agriculture. However, it is necessary to deepen the analysis of the effects of ENSO and other seasonal phenomena on yields. Being also necessary more information on the attitudes of the Pampas producers and the different management alternatives available against these forecasts.